Antioxidant Activity and Cytotoxic Effects of Hypnea musciformis on MCF7 and MDA-MB-231 Cell Lines: Effects of Silver Nanoparticle and L-carnitine on Mixed Vaginitis - Moulazadeh, Alireza; Ranjbar, Razieh; Dakhili Ardestani, Amin; Najafipour, Sohrab (Iranian Journal of Pharmaceutical Sciences, 2021)
Free radicals impair the cellular and tissue homeostasis, which can cause to cancer. Hypnea musciformis is a red seaweed and rich source of secondary antioxidant metabolites. These metabolites probably are effective in cancer treatment. In the present study, the phenolic and flavonoid content of the hydro-methanolic extract of Hypnea musciformis were determined respectively by the Folin-Ciocalteu and aluminum-chloride assay. The monovalent reducing power and total radical scavenging activity of the extract were also evaluated respectively by FRAP and DPPH assay. The cytotoxic effects of the extract were evaluated by MTT assay on MDA-MB-231 and MCF7 cell lines. Morphological changes of the cell lines were also examined by invert microscope. Statistical analysis was performed using t-test in GraphPad Prism 8.0.2 software. The results of the study indicate that the phenolic and flavonoid contents of the extract respectively were 14.05± 2.39 μgGAE/mg and 39.08± 8.78 μgQE/mg. The monovalent reducing power of the extract was 243.32± 27.86 μmol Fe2+/g and its total radical scavenging activity (in 1000 μg/mL) was 18.75± 1.51 %. The cytotoxic effects of the extract on MDA-MB-231 were higher than MCF7 cell line, significantly (P <0.05). The IC50 value of the extract on MDA-MB-231 and MCF7 cells respectively was 634.5 and 826.8 μg/mL, after 72 hours of incubation. The morphological changes of treated cell line include cell granulation, cell contraction and rupture in a concentration and time dependent pattern. The cytotoxic effects of Hypnea musciformis extract were not dependent on estrogen, progesterone and HER2 receptors. Therefore, the hydro-methanolic extract of Hypnea musciformis probably is a favorable option in drug discovery against the triple-negative tumors.